Techniki graficzne w procesie segmentacji rynku na podstawie danych symbolicznych - Wilk, Justyna (Visualization Techniques in Market Segmentation Procedure Based on Symbolic Data, 2009)
Market segmentation is a key strategic management tool. It enables to meet the customers' needs more precisely, gain a higher market share and profits. Marketing information is collected through questionnaire surveys or from data bases. The data complexity prevents application of classical data to describe customers. Symbolic data application allows us to describe customers in an explanatory way. Implementing of the market segmentation strategy requires a thorough understanding of the research results. Visualization techniques application simplifies communicating the findings to practitioners. The aim of the paper is to introduce visualization techniques that can be applied in market segmentation research based on symbolic data.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 153-164